The more, the merrier: a new colonial species of the orb weaving spider genus Leucauge White, 1841 (Araneae: Tetragnathidae) from the Amazon rainforest - Ferreira-Sousa, Leonardo; Venticinque, Eduardo Martins; Motta, Paulo César; Brescovit, Antonio Domingos (Zootaxa, 2023)
A new Leucauge species, widespread in the Amazon rainforest, is described and illustrated. Leucauge behemoth n. sp. lives in colonies, usually positioned above turbulent waters. Both males and females have a unique color pattern, especially on the abdomen, which makes this species easily identifiable. Males are distinguished from most congeners by the long hook of the cymbium and from their closest relatives by the lack of a cymbial dorsobasal process. Females of this species differ from their congeners by the presence of a rounded ventral process in the epigynum. Leucauge argyroaffins Soares & Camargo, 1948 is proposed as a junior synonym of Leucauge argyra (Walckenaer, 1841).